1945
DOI: 10.1042/bj0390213
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of wheat and rye and of flours derived therefrom

Abstract: Considering the outstanding importance of wheat to man, curiously few comprehensive studies of its chemistry have been made. It is, however, well known that variety, soil and climate all affect the chemical composition of wheat. Our knowledge of the subject was summarized in broad fashion by Booth, Carter, Jones & Moran (1941 a, b), whilst a detailed survey of the literature has since been published by Bailey (1944). Both these publications indicate the lack of precise information on the general chemistry of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1947
1947
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Tannins were estimated with Folin-Dennis reagent (1.5 ml) (AOAC 1960) on extracts of samples (2.5 g) boiled with deionized water (75 ml, 30min) centrifuged (910 x g, 20min) and colour was developed with sodium bicarbonate (0.5 ml of 35%) and Folin-Dennis reagent, read at 400nm. Phytate phosphorus was estimated as per McCance et al (1945), by extracting dry powder (3 g) with HCl(l.5 N, 5 ml) at 37°C for 2 h. After centrifugation (910 x g, 1Omin) supernatant (0.5 ml) was neutralize,d with 0.5 N NaOH and then made slightly acidic before adding FeC13 (2ml,0.25%) and heating ( l W C , 20min). The precipitate was centrifuged (1140 X g, 15min), washed with 0.17N HCI, treated with 5N NaOH (1 ml) and then mixed with concentrated H2S04 (1 ml) plus 60% perchloric acid (1 ml), cooled and estimated colorimetrically using meta-vanadate reagent.…”
Section: Methodsmentioning
confidence: 99%
“…Tannins were estimated with Folin-Dennis reagent (1.5 ml) (AOAC 1960) on extracts of samples (2.5 g) boiled with deionized water (75 ml, 30min) centrifuged (910 x g, 20min) and colour was developed with sodium bicarbonate (0.5 ml of 35%) and Folin-Dennis reagent, read at 400nm. Phytate phosphorus was estimated as per McCance et al (1945), by extracting dry powder (3 g) with HCl(l.5 N, 5 ml) at 37°C for 2 h. After centrifugation (910 x g, 1Omin) supernatant (0.5 ml) was neutralize,d with 0.5 N NaOH and then made slightly acidic before adding FeC13 (2ml,0.25%) and heating ( l W C , 20min). The precipitate was centrifuged (1140 X g, 15min), washed with 0.17N HCI, treated with 5N NaOH (1 ml) and then mixed with concentrated H2S04 (1 ml) plus 60% perchloric acid (1 ml), cooled and estimated colorimetrically using meta-vanadate reagent.…”
Section: Methodsmentioning
confidence: 99%
“…Benjamin (1943) also found that the increase of height of London schoolchildren in 1935-38 was maximum in late spring and minimum in mid-autumn. In the rate of growth of boys a t two public schools seasonal variations were observed by Widdowson and McCance (1944) which might be related to observed seasonal changes in the metabolism of calcium (McCance and Widdowson, 1943).…”
Section: Rate Of Groiuthmentioning
confidence: 98%
“…London children suffered more than children in most towns from the effects of bombing; it is not surprising that their growth should have been affected. No deterioration of average height and weight was found among boys and girls at public schools by Armattoe (1943, 1, 2) in 1942, or by Billington, McCance and Widdowson (1943) among boys in 1943. I n Cambridge, which is not included in Bransby's 21 localities, schoolchildren were appreciably heavier on the average in 1943 than in 1942.…”
Section: Height and Weight Increasementioning
confidence: 99%
See 1 more Smart Citation
“…Their nitrogen contents were equalized by adding potato starch in the first and second series of ,experiments and by adding sucrose in the third series. Further, in the experiments with whole wheat meal, the daily food intake was raised from 7-5 to 7-85 g./100 g. body weight in order to allow for the low content of utilizable calories in whole wheat (McCance, Widdowson, Moran, Pringle & Macrae, 1945 t (NS), not significant; (S), significant at the 5 % level; (SS) significant at the 1 % level.…”
Section: Disappearance Of Labile Liver Cytoplasm In Protein Deficiencymentioning
confidence: 99%